Stabilization of Clay Subgrade Soil by Using Waste Foundry Sand with a Geogrid - Qais Sahib Banyhussan; Jaafar Abdulrazzaq; Ahmed A. Hussein; Anmar Dulaimi; Jorge Miguel de Almeida Andrade; Luís Filipe Almeida Bernardo (CivilEng, 2025)
Various stabilizers, such as jute, gypsum, rice-husk ash, fly ash, cement, lime, and discarded rubber tires, are commonly used to improve the shear strength and overall characteristics of clay subgrade soil. In this study, waste foundry sand (WFS) is utilized as a stabilizing material to enhance the properties of clay subgrade soil and strengthen the bond between clay subgrade soil and subbase material. The materials employed in this study include Type B subbase granular materials, clay subgrade soil, and 1100 Biaxial Geogrid for reinforcement. The clay subgrade soil was collected from the airport area in the Al-Muthanna region of Baghdad. To evaluate the effectiveness of WFS as a stabilizer, soil specimens were prepared with varying replacement levels of 0%, 5%, 10%, and 15%. This study conducted a Modified Proctor Test, a California Bearing Ratio test, and a large-scale direct shear test to determine key parameters, including the CBR value, maximum dry density, optimum moisture content, and the compressive strength of the soil mixture. A specially designed large-scale direct shear apparatus was manufactured and utilized for testing, which comprised an upper square box measuring 20 cm × 20 cm × 10 cm and a lower rectangular box with dimensions of 200 mm × 250 mm × 100 mm. The findings indicate that the interface shear strength and overall properties of the clay subgrade soil improve as the proportion of WFS increases.